New system design for the cultivation of extractive species at exposed sites - Part 1: System design, deployment and first response to high-energy environments. (May 2021) - Heasman, Kevin G.; Scott, Nicholas; Smeaton, Malcolm; Goseberg, Nils; Hildebrandt, Arndt; Vitasovich, Peter; Elliot, Andrew; Mandeno, Michael; Buck, Bela H.
Abstract: The purpose of this publication is to perform a system analysis of new cultivation technology for exposed bivalve farming. The technical feasibility of the new construction, called Shellfish Tower, was assessed. The device has gone through several very different phases of development on its way to the deployment of the prototype. These included multiple iterations during the designing stage, wave tank testing, fabrication, loading and unloading on trucks and vessels, deployment at sea, installation and assembly on the single mooring line, and bring it to its final position in a submerged mode 5m-10 m below the water surface. The final structure has a hexagonal body, with a centrally orientated variable buoyancy unit with culture sub-units on each of the six corners. These sub-units can be used for the culture of oysters ( Magallana gigas – formally Crassostrea gigas ) as well as for the collection of mussel spat ( Perna canaliculus ). Other possible candidates could be seaweed, lobsters, sponges or tunicates. The operational depth of the whole system can be at any depth but was tested at between 5 and 10 m below the water surface positioned on the mooring line between the screw anchor and surface floats for the prototype tests. The system was deployed in March 2019 six nautical miles off the Bay of Plenty, North Island (New Zealand), in exposed waters near a commercial mussel farm and has been in test mode since then. The modelled structure indicates a design tolerance of significant wave height of over 7 m and currents of over 0.8 m/s. Initial results show that the new design has survived waves at 4.6 m significant height and current velocities of up to 0.7 ms -1, while showing best growth conditions of the cultured oysters as well as for the spat settlement of juvenile greenshell™ mussels.